2017
DOI: 10.1111/pala.12290
|View full text |Cite
|
Sign up to set email alerts
|

Fossilization processes of graptolites: insights from the experimental decay of Rhabdopleura sp. (Pterobranchia)

Abstract: Laboratory experiments documenting the decomposition pattern of extant organisms are used to reconstruct the anatomy and taphonomy of fossil taxa. The subclass Graptolithina (Hemichordata: Pterobranchia) is a significant fossil taxon of the Palaeozoic era, represented by just one modern genus, Rhabdopleura. The rich graptolite fossil record is characterized by an almost total absence of fossil zooids. Here we investigated the temporal decay pattern of Rhabdopleura sp. tubes, stolons and single zooids removed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…; Beli et al . ). Of the ten taphonomic characters scored (Table ), four may be used to evaluate stemward slippage: carapace completeness, claw completeness, abdomen completeness and telson completeness.…”
Section: Discussionmentioning
confidence: 97%
“…; Beli et al . ). Of the ten taphonomic characters scored (Table ), four may be used to evaluate stemward slippage: carapace completeness, claw completeness, abdomen completeness and telson completeness.…”
Section: Discussionmentioning
confidence: 97%
“…[51] The same decay experiments allowed the chevron-shaped structures in Conopiscius, a Carboniferous chordate, to be interpreted as myomeres rather than external scales, and also indicated that a decay-resistant cuticle was not necessarily present in Pikaia from the Burgess Shale. [51,55] Decay in seawater has now been monitored in a range of taxa in laboratory experiments (see Table S1, Supporting Information): anthozoans, [56] annelids, [48] chaetognaths, [57] priapulids, [18] onychophorans, [17] pterobranchs, [58] enteropneusts, [59] nonvertebrate chordates, [20] and cyclostomes. [60] Thus the sequence of character loss has been determined for taxa representing most clades of eumetazoans.…”
Section: Boxmentioning
confidence: 99%
“…While the chitinous perisarc and hydrothecae of colonial hydrozoans may have some fossilization potential, it is rather unlikely that the coenosarc would be preserved in the fossil record. By contrast, decay experiments on modern pterobranchs have demonstrated that the sclerotized stolon system is one of the most durable structures of pterobranch colonies and may prevail until most of the zooids and tubarium have decayed (Beli et al, 2017). In Malongitubus , and notably also in the closely related Dalyia racemata from the Cambrian Stage 5 Burgess Shale, the putative stolon system is the most resistant structure of the fossil remains.…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…Taphonomic experiments on modern pterobranchs (Briggs et al, 1995; Beli et al, 2017) show different rates of decay between zooids, tubaria, and the stolon system. The zooids decay rapidly and become unrecognizable after a few days, whereas the tubes and the interior stolon system can last for several months.…”
Section: Systematic Paleontologymentioning
confidence: 99%